Development of Immunochromatographic Strip Tests for Selective and Quantitative Detection of Melamine - Wicaksono, Wiyogo P.; Ivandini, Tribidasari A.; Saepudin, Endang; Einaga, Yasuaki (Makara Journal of Science, 2014)
An immunochromatographic strip test based on the complex reaction of antigen-antibody (melamine-antimelamine) was developed for quantitative detection of melamine. Gold nanoparticles (AuNP) were used to form AuNP-labeled antibody, which then acted as a biosensor. Melamine quantification was performed by the determination of AuNP using anodic stripping voltammetry technique with a boron-doped diamond as the working electrode. With sample volume of 100 µL and immunoreaction time of 7 min, the developed immunochromatographic strip test produced a linear calibration curve for melamine concentration range of 0–0.6 mg/L, with detection limit of 0.1 mg/L and RSD of ~5%. Furthermore, negative results were obtained for samples containing cyanuric acid and urea, indicating that the developed immunochromatographic strip test has potential for selective and quantitative detection of melamine.